Effect of group psychological training based on gratitude and resilience on sense of meaning in life and psychological well-being among college students - HANG Peng; PENG Li; XU Chen (陆军军医大学学报, 2024)
Objective To explore the relationship of gratitude, resilience and meaning in life with psychological well-being, and determine the effect of group psychological training based on gratitude and resilience on the sense of meaning in life and psychological well-being in college students. Methods Based on advantage of mental health course for college students, cluster sampling was used to subject 138 students from a certain university. The participants were randomly divided into intervention group (n=70) and control group (n=68). The intervention group received 5 weeks of group psychological training, once a week for 2 h, while the control group did not receive such training for the time being (the participating received the same content training next semester). Self-designed demographic questionnaire, Meaning in Life Questionnaire (MLQ), Gratitude Question (GQ), 10-item Connor-Davidson Resilience Scale (CD-RISC-10) and Chinese version of Ryff's Scales of Psychological Well-Being (RPWB) were employed to evaluate the 2 groups before intervention (T1), and immediately (T2) and 1 month after intervention (T3). The data at T1 was used to analyze the relationship between variables. Results ① Gratitude, resilience, meaning in life and psychological well-being were positively correlated with each other (P < 0.01), and meaning in life played a mediating role between gratitude and psychological well-being, and between psychological resilience and psychological well-being. ② Before training, no significant differences were seen in demographic data and psychological indicators between the 2 groups. After training, the interaction effect between time and group was significant for gratitude, resilience, meaning in life, and psychological well-being. The intervention group had significantly higher scores of gratitude, resilience, meaning in life, and psychological well-being than the control group at T2 and T3 (P < 0.01). The scores for gratitude, psychological, meaning in life, and psychological well-being in the intervention group at T2 and T3 were significantly higher than those at T1 (P < 0.01). There were no statistical differences in scores for gratitude, psychological resilience, meaning in life, and psychological well-being between T2 and T3 in the intervention group. Conclusion Meaning in life partially mediates the relationship between gratitude and resilience and psychological well-being. Group psychological training based on gratitude and psychological resilience can significantly improve the levels of gratitude, resilience, meaning in life and psychological well-being in college students, and has a lasting effect.